La primauté du droit : la situation des immigrants et des réfugiés en droit canadien au regard des Chartes et des textes internationaux - Brunelle, Christian (Les Cahiers de droit, 1987)
The « rule of law » which for a long time was considered as an unwritten part of the Constitution now enjoys full constitutional status. Its enshrining in the preamble of the Canadian Charter sheds considerable light on the manner in which the rights and freedoms of the Charter should be perceived. The author opens his discussion by examining the impact that the constitutionalization of the « rule of law » has had on immigrants and refugees in Canada. As the Immigration Act of 1976 confers numerous discretionary powers which could result in their abusive use, the author analyses how the Human Rights charters applicable in Canada and in Quebec can insure the legal protection of immigrants and refugees. In the second part of his study, the author discusses the principal international texts ratified by Canada which have as their purpose the protection of the rights of immigrants and refugees. As international law is not « self-enforcing » in Canada, the author shows how the internal legal community conforms to the international obligations contracted by Canada.